Comparison of Medicaments Used in Regenerative Endodontics in Terms of Dentin Microhardness and Adhesion of Mineral Trioxide Aggregate - Saricam, Esma; Bulak, Neslihan; Özyurt, Esra; Özcan, Suat (UI Scholars Hub, 2020)
Eliminating microorganisms in the root canal system is important for the success of regenerative endodontics. Objective: This study evaluated the effects of different antibiotic pastes used for regenerative endodontic procedures on dentin microhardness and the push-out bond strength of mineral trioxide aggregate (MTA) to root canal dentin. Methods: Sixty-four maxillary central incisors were instrumented and randomly divided into the following four groups (n = 16) for medicament treatment: triple antibiotic paste, amoxicillin+clavulanic acid, cefaclor, and control (no dressing). After 21 days, two root segments were obtained by sectioning the roots horizontally for push-out and microhardness evaluations. MTA was placed into the root canal of the sectioned segment for the push-out test. In the microhardness evaluation, three indentations were made at 500 and 1,000 μm from the canal lumen. The arithmetic mean was then calculated for each distance. ANOVA with post hoc Scheffe test and t test were used for the statistical analyses. The significance level was set at p < 0.05. Results: No significant difference was found between the groups in terms of push-out bond strength (p > 0.05). Cefaclor and amoxicillin+clavulanic acid reduced the microhardness values of the dentin at 500 μm (p < 0.05) while cefaclor had the lowest value at 1,000 μm (p < 0.05). Conclusion: Cefaclor reduced the microhardness value more than the other medicaments did at a depth of 1,000 μm. The pastes provided similar adhesion of MTA.